Prediction of Accident Numbers in Yogyakarta using The Single Moving Average Method - Darmawan, Rizcki Dwi (KH. A. Wahab Hasbullah University, 2022)
The soaring birth rate of the Indonesian people causes an increase in the number of private vehicles which causes an increase in the number of accidents. The purpose of this article is to predict the number of accidents using the Single Moving Average technique. This article uses data originating from the Yogyakarta government's dataku web application with a period from 2010 to 2021 in an annual period. Predictive models were checked using RMSE, MAD, and MAPE. Using the Single Moving Average technique, the error value for RMSE is 643.99, MAD is 494.7, and MAPE is 1036.17%.